Թեոդորետոս Կյուրացու Սաղմոսաց մեկնությունը՝ Վարդան Արեւելցու Սաղմոսաց մեկնության աղբյուր - Քյոսեյան, Հակոբ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Сопоставление толкования Псалмов Феодорита Кирского, источника толкования псалмов Вардана Аревелци Эпипан Кипрский (= Феодорит Кирский, 457) и сочинений Вардана Аревелци (1271) с одной стороны подчеркивает влияние, которое толкование Кюрийца оказало на сочинение Аревелци, а с другой становится новым свидетельством присутствия в армянской действительности «Гексапла» Оригена. В статье раскрывается также способ пользования первоисточником Вардана Аревелци (не дословно). Theodoret of Cyrus’ “Commentary on the Psalms” served as a source for Vardan Areveltsi’s “Commentary on the Psalms”. The combination of works by Epiphanius of Cyprus ((= Theodoret of Cyrus),) and Vardan Areveltsi, on the one hand, reveals the influence that Theodoret of Cyrus’ “Commentary” had upon the work of Vardan Areveltsi, and on the other hand, it becomes itself a new evidence of the presence of Origen’s “Hexapla” in the Armenian literature. The article also reveals the method (non-verbatim) Vardan Areveltsi used dealing with sources.
Keywords: Կրոնագիտություն; Փիլիսոփայություն